Exploring the relationship between mental health status and life events in children and adolescents: the role of mediating factors - Xie, Jiemei; Cheng, Guoqiang; Zhou, Mingliang; Liang, Qisheng; Wang, Qianjin (Frontiers in Psychiatry, 2025)
BackgroundThe mental health status of children and adolescents is significantly influenced by negative life events, yet there is a lack of comprehensive analysis on mediating factors. This study aims to examine the relationship between negative life events and symptoms of anxiety and depression in children and adolescents, as well as to identify potential mediating factors.MethodsIn May 2022, cluster-randomized sampling was used to select 8041 primary, middle, and high school students in Zhaoqing City, Guangdong Province, for the final analysis. The Adolescent Life Events Scale, Self-Rating Anxiety Scale, and Self-Rating Depression Scale were employed to assess negative life events, anxiety symptoms, and depressive symptoms, respectively. Pearson correlation analysis and linear regression analysis were utilized to identify risk factors, and the Bootstrap method was applied for mediation analysis.ResultsThe study revealed that 80.52% of children and adolescents experienced negative life events, with 23.38% reporting anxiety symptoms and 42.57% reporting depressive symptoms. Significant positive correlations were observed between negative life events and anxiety symptoms (r = 0.32, p < 0.001), as well as depressive symptoms (r = 0.44, p < 0.001). Mediation analysis further demonstrated that anxiety and depressive symptoms acted as mutual mediators in the relationship between negative life events and each other.ConclusionsThis study underscores the complex interplay between anxiety, depression, and negative life events in children and adolescents. These findings can inform strategies to help mitigate the emotional impact of negative life events, enhance mental health, and provide a scientific basis for developing effective interventions.